2021
DOI: 10.1111/grow.12572
|View full text |Cite
|
Sign up to set email alerts
|

Spatial‐temporal evolution and influence factors of China’s agricultural non‐point source pollution discharge intensity in recent 40 years

Abstract: The excessive use of agricultural chemicals and the unreasonable use of agricultural wastes are the main problems encountered by China's agriculture department.However, the comprehensive study on the discharge intensity of China's agricultural non-point source pollution (ANPSP) under the long-term series has not been fully explored. On the basis of our previous research, the spatial-temporal characteristics and influence factors of ANPSP discharge intensity in China from 1978 to 2017 were analyzed. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…(3) Selection of influencing factors Referring to relevant studies on the analysis of factors influencing ANSP, it can be found that scholars' selection of factors influencing ANSP mostly revolves around industrialization, affluence, population size, planting scale, and planting structure [52,[54][55][56][57]. Combined with the development background of rapid industrialization in Gongyi city, this study used industrialization as the core explanatory variable.…”
Section: Spatial Econometric Model (1) Spatial Measurement Model Cons...mentioning
confidence: 99%
“…(3) Selection of influencing factors Referring to relevant studies on the analysis of factors influencing ANSP, it can be found that scholars' selection of factors influencing ANSP mostly revolves around industrialization, affluence, population size, planting scale, and planting structure [52,[54][55][56][57]. Combined with the development background of rapid industrialization in Gongyi city, this study used industrialization as the core explanatory variable.…”
Section: Spatial Econometric Model (1) Spatial Measurement Model Cons...mentioning
confidence: 99%
“…Effective governance of farmland non‐point source pollution (FNSP), which is related to multiple sustainable development goals (SDGs) such as food safety, ecological security, clean drinking water, and climate change (Abbass et al, 2022), faces enormous challenges. As the world's largest developing country, China's agricultural production has made remarkable progress in the last 40 years (Xu et al, 2022) but at the cost of severe FNSP, causing widespread social concern (Zou et al, 2022). In response, the Chinese government shifted its goal to the green transformation of agriculture in 2015 for sustainable development (Mao, 2021), wherein “one control, two reductions, and three basics” (CRB) † functions as the primary policy framework for FNSP governance (State Council Information Office, 2015).…”
Section: Introductionmentioning
confidence: 99%